Working with an Accent: The Aesthetic Labour of International Teaching Assistants in Ontario Universities - Ramjattan, Vijay Anil (University of Toronto, Ontario Institute for Studies in Education, 2019)
International teaching assistants (ITAs) in North American English-medium universities often work with an accent. In one sense, to work with an accent entails doing one’s work while having an aural stigma. This is due to the increased likelihood that students and other university stakeholders perceive ITAs’ foreign-accented English as difficult to understand. The purported problem of their foreign accents can thus create additional facets in working with an accent such as working with the idea of how to change an accent and performing (around) it in order to be viewed as effective workers. All of this work can be considered a type of aesthetic labour in that ITAs need to develop the right sound for their professional duties. Based on a narrative inquiry of the experiences of 14 ITAs working in various universities in Ontario, Canada, this thesis explores how they conceptualize and execute aesthetic labour. Specifically, it details their perceptions of a satisfactory aural aesthetic for work as well as the extent to which they incorporate this aesthetic in discussions about their professional practices. Regarding the first research objective, the ITAs understood a satisfactory accent in linguistic, racial, and professional terms. Indeed, an accent could sound “native” or “nonnative,” become “whitened” or remain racialized, and match or not match one’s work (environment). In terms of taking up these perceptions in their professional practices, which took the general form of working on or around an accent, the ITAs’ prior views on aural aesthetics were upheld and/or tempered by contextual factors in their universities. On the immediate level, the above findings provide suggestions for changes to existing forms of ITA training, which tend to ignore the knowledge of ITAs and fail to prepare them to effectively communicate according to the specificities of their work environments. More broadly, the findings are useful in highlighting how accents are not stable individual traits, but rather, malleable tools that help workers negotiate intercultural encounters in a range of professional settings. Therefore, this study counters research that frames the ITA accent as an inherent problem needing to be rectified for a homogeneous audience.